2009
DOI: 10.1108/17574320910942178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cultural values on young consumers' choice of international tertiary education

Abstract: PurposeThe purpose of this paper is to investigate the following choice issues among young consumers (Generation Y): how cultural values influence a student's decision on study destinations, and how cultural values influence student's preferred sources of information for university choice?Design/methodology/approachHigh school students from Singapore and Malaysia, intending to study in New Zealand were surveyed with an instrument based on Schwartz's Value Survey and the understanding that cultural values are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Research by Chung, Fam & Holdsworth, (2009) reported how social and cultural factors are important predictors that shape the enrollment decisions for college-going students. Other research refers to the impact of significant others, i.e., parents, teachers, and friends who serve as role models, and influence the hopes and aspirations of college goers (Hossler, Braxton & Coopersmith, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Research by Chung, Fam & Holdsworth, (2009) reported how social and cultural factors are important predictors that shape the enrollment decisions for college-going students. Other research refers to the impact of significant others, i.e., parents, teachers, and friends who serve as role models, and influence the hopes and aspirations of college goers (Hossler, Braxton & Coopersmith, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Data non-normality is assumed to be noncritical where a substantial sample size (e.g. 200 or more) is used (Hair et al, 2014) with a multivariate data analysis using maximum likelihood approximation in AMOS (Chung et al, 2009). Yet we assessed data normality by calculating skewness and kurtosis values (Hasan and Kashif, 2021;Tandon et al, 2021).…”
Section: Data Normality and Methods Biasmentioning
confidence: 99%
“…200 or more) is used (Hair et al. , 2014) with a multivariate data analysis using maximum likelihood approximation in AMOS (Chung et al. , 2009).…”
Section: Methodsmentioning
confidence: 99%
“…There are many research studies about factors influencing student"s university choice in the world, these can be categorize in three level containing national levels (Bidet and Newman, 2001), international level (e.g. Choy Chung, 2009), and both (Kee Ming, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%